«Քելեկյան» և «Սիսվան» որբանոցների գործունեությունը - Սահակյան, Վերա («Նաիրի» հրատ.)
Мемуары Самвела Пораняна, написанные на турецком языке армянской графикой, были пересланы в Армению из Дамаска через иммигранта Арутюна Паляна, и он в год пятидесятилетия Геноцида армян перевел их на армянский и подготовил к печати. Однако, по каким-то обстоятельствам они остались неопубликованными и преданы забвению. В рамках настоящей статьи проделана попытка извлечь из них некоторые подробности о деятельности сиротских приютов “Келекян” и “Сисван”. Samvel Poranyan's memoirs written in Turkish in Armenian characters were brought to Armenia from Damascus in 1946 by Harutyun Palyan. He translated them into Armenian and prepared for publication on the occasion of the 50th anniversary of the Armenian Genocide. But for some reasons they remained unpublished and were completely forgotten. In the present article we try to elucidate the foundation and activities of the “Kelekyan” and “Sisvan” orphanages on the basis of information drawn from these and several other unpublished memoirs.
Keywords: Գիտաժողովի նյութեր; Որբախնամ կառույցներ